Integrative Empowerment Of Health Cadres In Efforts To Monitor Stunting Risk Through The Use Of Smartphone-Based Electronic Child Card Applications In Ngiliran Village, Panekan District, Magetan Regency - Wisnu, Nurwening Tyas; Suharto, Agung; Purwanto, Triana Septianti; Herlina, Tutiek; Sumasto, Hery (Frontiers in Community Service and Empowerment, 2024)
ABSTRACT The Community Engagement activity, conducted from May to August 2024, aimed to empower various stakeholders, such as early childhood integrated health service cadres, prospective brides and grooms, pregnant women, and mothers of young children, in their endeavors to monitor early stunting effectively. It addressed the pressing issue of stunting prevalence in Ngiliran Village, which had reached an alarming 18.6%, surpassing the national target set for 2024, which is 14%. Partners, including integrated health service cadres, prospective brides and grooms, pregnant women, and mothers, faced challenges like limited knowledge in measuring children's nutritional status, inconsistent monitoring, and inadequate stunting prevention education. To address these issues, the activity utilized the Electronic Child Card (KARANEL) smartphone application. KARANEL accurately measured children's height and weight, stored data electronically, presented nutritional status visually, and offered guidance. It empowered partners to identify, prevent, and manage stunting effectively. The results demonstrated that KARANEL enhanced the knowledge, skills, and motivation of integrated health service cadres and partners. Conclusion: the smartphone-based KARANEL application proved highly beneficial for early stunting monitoring in Ngiliran Village, providing a practical solution to combat stunting